DIGITAL LITERACY IN 21ST CENTURY: A PORTRAYAL OF an ONLINE EFL CLASS in INDONESIA - yavani, zakky; nurmala, Mela; arrasyid, Farouk imam (STIT Buntet Pesantren Cirebon, 2022)
Abstract ___________________________________________________________________ The dominance of technology in everyday life emphasizes the importance of digital literacy for people all over the world. Demand for digital literacy integration penetrates all aspects, including the teaching and learning process in Indonesia. Many researchers have already explored digital literacy in the classroom and observed it in English classroom-based learning. However, to depict more what factors are needed to develop digital literacy in online EFL classes are not many, mainly in the Indonesian context. To investigate the case, this study employed a qualitative case study approach using the following instruments; a semi-structured interview with a knowledgeable English teacher in utilizing technology, online classroom observation, and documentation. The data were then analyzed, interpreted, and presented using descriptive explanation. First, it was found that students used various digital tools and performed several digital literacy elements (cultural, cognitive, communicative, and critical) in English online learning. Nevertheless, the lack of technology sources and students' readiness in utilizing technology are regarded as barriers to implement digital literacy in practice. Second, to develop digital literacy in English online learning, students are required to use various digital tools and to recognize a variety of features across digital tools, communicate appropriately with teachers and classmates through digital tools, as well as use technology to evaluate information. So, the guidance from the teacher regarding aspects of digital literacy, and students' involvement in multiple digital environments are considered as the needs of students to develop digital literacy in the 21st century.